Two-Photon Imaging to Unravel the Pathomechanisms Associated with Epileptic Seizures: A Review - Luqman Khan; Rick van Lanen; Govert Hoogland; Olaf Schijns; Kim Rijkers; Dimitrios Kapsokalyvas; Marc van Zandvoort; Roel Haeren (Applied Sciences, 2021)
Despite extensive research, the exact pathomechanisms associated with epileptic seizure formation and propagation have not been elucidated completely. Two-photon imaging (2PI) is a fluorescence-based microscopy technique that, over the years, has been used to evaluate pathomechanisms associated with epileptic seizures and epilepsy. Here, we review previous applications of 2PI in epilepsy. A systematic search was performed in multiple literature databases. We identified 38 publications that applied 2PI in epilepsy research. These studies described models of epileptic seizure propagation; anatomical changes and functional alterations of microglia, astrocytes, and neurites; and neurometabolic effects that accompany seizures. Moreover, various neurovascular alterations that accompany seizure onset and ictal events, such as blood vessel responses, have been visualized using 2PI. Lastly, imaging and quantitative analysis of oxidative stress and the aggregation of lipofuscin in the neurovasculature have been accomplished with 2PI. Cumulatively, these papers and their reported findings demonstrate that 2PI is an especially well-suited imaging technique in the domain of epilepsy research, and these studies have significantly improved our understanding of the disorder. The application of 2PI provides ample possibilities for future research, most interestingly on human brains, while also stretching beyond the field of epilepsy.